Poly(2-ethyl-2-oxazoline) bottlebrushes: How nanomaterial dimensions can influence biological interactions. (15th May 2021) - Pizzi, David; Mahmoud, Ayaat M.; Klein, Tobias; Morrow, Joshua P.; Humphries, James; Houston, Zachary H.; Fletcher, Nicholas L.; Bell, Craig A.; Thurecht, Kristofer J.; Kempe, Kristian
Graphical abstract: Abstract: Biocompatible polymers are crucial components of successful nano-sized carriers, which enable the delivery of otherwise largely ineffective therapeutics. Poly(2-ethyl-2-oxazoline) (PEtOx) is one polymer that has shown potential for this application due to its demonstrated low fouling nature and biocompatibility comparable to the current gold standard carrier, poly(ethylene glycol). PEtOx based bottlebrushes, in particular, are promising therapeutic carriers due to their anisotropic nature, which can be easily fine-tuned. Despite this potential, little is known about the interaction of PEtOx bottlebrushes with biological systems. The present study provides a detailed insight into the cellular interactions and biodistribution of PEtOx bottlebrushes in a mouse model. Three PEtOx bottlebrushes of varied side-chain and backbone lengths were designed to highlight the effect that the degree of polymerisation (DP) of each aspect may have on both cellular interaction and biodistribution. Herein we show that PEtOx bottlebrushes display no adverse effects to either cells or mice over 48 h at doses that would be relevant to drug delivery applications. Furthermore, increasing either the backbone or side-chain length of PEtOx bottlebrushes leads to a reduction in cellular association in vitro and an increase in blood circulation times in vivo . The fact that small changes to the dimensions of the PEtOx bottlebrushes have a marked effect on biodistribution and blood circulation times may prove to be a highly beneficial insight for the design of next-generation PEtOx bottlebrushes nanocarriers with tailor-made profiles dependent on the application required.